2008
DOI: 10.1590/s1806-37132008000800008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo descritivo da freqüência de micobactérias não tuberculosas na Baixada Santista (SP)

Abstract: OBJETIVO: Este estudo teve por objetivo descrever a freqüência das espécies de micobactérias não tuberculosas (MNT) identificadas laboratorialmente a partir do isolamento de sítios não estéreis (escarro) de indivíduos infectados ou não pelo vírus HIV na Baixada Santista (SP), período de 2000 a 2005. MÉTODOS: Foi realizada análise retrospectiva dos resultados de baciloscopia e cultura, disponíveis nos registros do laboratório regional de tuberculose, Instituto Adolfo Lutz-Santos. RESULTADOS: Analisou-se 194 cep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
8
0
3
Order By: Relevance
“…RGM species, including M. abscessus , M. massiliense , M. bolletii (formally M. abscessus species) represented almost 45% of all NTM pulmonary cases, whereas in Sao Paulo, M. avium complex (MAC) and M. kansasii represent the most common NTM in pulmonary disease [51], [52]. In addition, when stratifying to the NTM species level, we observed that gender associated infection was even more pronounced in the case of M. chelonae-M. abscessus complex (∼45% females), especially M. massiliense (34.5%).…”
Section: Discussionmentioning
confidence: 99%
“…RGM species, including M. abscessus , M. massiliense , M. bolletii (formally M. abscessus species) represented almost 45% of all NTM pulmonary cases, whereas in Sao Paulo, M. avium complex (MAC) and M. kansasii represent the most common NTM in pulmonary disease [51], [52]. In addition, when stratifying to the NTM species level, we observed that gender associated infection was even more pronounced in the case of M. chelonae-M. abscessus complex (∼45% females), especially M. massiliense (34.5%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the species isolated from the Ugandan ecosystems have been found to cause disease in patients in other parts of the world. For example bacteria in the M. avium complex are known to cause opportunistic infections in animals and humans [2], and have been isolated from cattle and humans with tuberculous lesions in Uganda [20,21], Zambia and other parts of the world [39,40]. M. simiae has been isolated from two Ugandan HIV infected patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…M. simiae has been isolated from two Ugandan HIV infected patients [41]. The other NTM detected in this study have been isolated from patients in different parts of the world, and may cause clinical syndromes: chronic bronchopulmonary disease, lymphadenitis, skin and soft tissue disease, skeletal disease, and disseminated and catheter-related infections [39,40,42-46]. In humans, immunocompromised individuals such as the malnourished, HIV/AIDS infected, children or the elderly are often affected [47].…”
Section: Discussionmentioning
confidence: 99%
“…Non-tuberculous mycobacteria were also sent to the Central Reference Lab for species identification by a phenotypic technique and molecular typing (PCR coupled to the Restriction Fragment Length Polymorphism - RFLP, and the analysis of a 441 bp fragment from the hsp65 gene (PRA-hsp65) 18 . …”
Section: Methodsmentioning
confidence: 99%